Analysis of Factors Influencing the Value of State-Owned Enterprises - Hasna, Fakhriah; Suprayitno, Gendut; Syarief Hidayatulloh, Furqon (PT Inovasi Pratama Internasional, 2025)
This study analyses the factors that influence the increase in the corporate value of State-Owned Enterprises (SOEs) with a Systematic Literature Review (SLR) approach using the Publish or Perish application in the 2019-2024 period. The search results show that macroeconomic variables, Good Corporate Governance (GCG) practices, government and public ownership, investment decisions, capital structure, Corporate Social Responsibility (CSR) disclosure, company growth, profitability, business risk, and financial risk are the main factors that have an impact on increasing the value of BUMN companies. These variables influence aspects of stability, transparency, asset management and corporate sustainability, all of which play an important role in attracting investor interest and supporting the long-term performance of SOEs. This study concludes that enhancing the enterprise value of SOEs requires comprehensive management of these factors to achieve sustainability and optimal growth in enterprise value.